2009
DOI: 10.1111/j.1525-1594.2009.00777.x
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of Early Postoperative Morbidity in Cardiac Surgery Patients Treated With Continuous Veno–Venous Hemofiltration During Cardiopulmonary Bypass

Abstract: Cardiac surgery with cardiopulmonary bypass is associated with a systemic inflammatory response syndrome. The major clinical features of this include a reduction of pulmonary compliance and increased extracellular fluids, with increased pulmonary shunt fraction similar to acute respiratory distress syndrome, thus resulting in prolonged mechanical ventilation time (VAM) and intensive care unit length of stay (ICU STAY). We evaluated the feasibility of an intraoperatory cardiopulmonary bypass (CPB) circuit conne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 10 publications
0
6
0
Order By: Relevance
“…A total of 646 abstracts and 20 full-text articles were assessed for eligibility, yielding 12 RCTs, consisting of 989 patients, that were included in the meta-analysis ( Table 1 ). 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 A large range was found in study publication dates (1997-2020); types of continuous ultrafiltration used in the intervention arm (CUF, ZBUF, SBUF, CUF-MUF); and types of cardiac intervention (coronary artery bypass grafting, valvular, concomitant coronary artery bypass grafting-valve, and aortic surgery). The intraoperative data from included studies are reported in Table 2 .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…A total of 646 abstracts and 20 full-text articles were assessed for eligibility, yielding 12 RCTs, consisting of 989 patients, that were included in the meta-analysis ( Table 1 ). 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 A large range was found in study publication dates (1997-2020); types of continuous ultrafiltration used in the intervention arm (CUF, ZBUF, SBUF, CUF-MUF); and types of cardiac intervention (coronary artery bypass grafting, valvular, concomitant coronary artery bypass grafting-valve, and aortic surgery). The intraoperative data from included studies are reported in Table 2 .…”
Section: Resultsmentioning
confidence: 99%
“…17 (2006) 100 CABG (NR) Valvular (NR) Excluded renal insufficiency CUF 63 ± 12 79 NR Low No UF 64 ± 10 74 NR Low Luciani et al. 18 (2009) 40 CABG (100) Excluded severe comorbidities SBUF 66.1 ± 11.1 NR NR Low No UF 65.2 ± 8.4 NR NR Low Santarpino et al. 19 (2009) 24 CABG (100) Elective, excluded LVEF < 40%, redo surgery, recent MI and severe comorbidities CUF 63.3 ± 9.2 75 ASA score: 3.1 ± 1.6 Low Steroids ∗ 59.3 ± 10.1 75 ASA score 2.8 ± 1.1 Low Zhang et al.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…[15] There isn't any standard definition of fluid load in current literature, and there is no guideline to manage it. [1,16] In the literature, prevention of fluid accumulation children has been associated with better survival, [17,18] and increased fluid load with increased mortality. [11,19] The first-line therapy to increase output in fluid management is diuretics.…”
Section: Discussionmentioning
confidence: 99%
“…Remo Luciani et al. (82) of the University of Rome, Rome, Italy evaluated the feasibility of an intraoperatory CPB circuit connected with a monitor for continuous venovenous hemofiltration (CVVH) to ameliorate pulmonary function after open heart surgery reducing mechanical ventilation time (VAM) and intensive care unit (ICU) stay. Forty patients undergoing elective coronary artery bypass grafting were randomized at the time of surgery into a control group (20 patients who received standard CPB) and a study group (20 patients who received CVVH during CPB).…”
Section: Cardiopulmonary Support and Membrane Oxygenationmentioning
confidence: 99%